On the discrepancy between the X-ray and UV absorption measurements of O VI in the local ISM - Gatuzz, Efrain; Garcia, Javier; Kallman, Timothy R. (Monthly Notices of the Royal Astronomical Society, 2019)
The total amount of OVI present in the interstellar medium ( ISM) obtained via absorption measurements in UV and X-ray spectra is currently in disagreement, with the latter being significantly larger ( by a factor of 10 or more) than the former. Previous works have proposed that the blend of the OVI K alpha line ( 22.032 angstrom) with the OII K beta-L12 line ( 22.04 angstrom) could account for the stronger absorption observed in the X-ray spectra. Here, we present a detailed study of the oxygen absorption in the local ISM, implementing our new model IGMabs which includes photoabsorption cross-sections of highly ionized species of abundant elements as well as turbulence broadening. By analysing high-resolution Chandra spectra of 13 low-mass X-ray binaries ( LMXBs) and 29 extragalactic sources, we have estimated the column densities of OI - OIII and from OVI - OVIII along multiple line-of-sights. We find that in most cases the OII K beta-L12 line accounts for <30 per cent of the total OVI K alpha + OII K beta. We conclude that the amount of OII predicted by our model is still insufficient to explain the discrepancy between X-ray and UV measurements of OVI column densities.
CRIS-Team WoS Importer:2019-09-03